TRPC absence induces pro-inflammatory macrophage polarization to promote obesity and exacerbate colorectal cancer - Lin, Yanting; Gao, Rui; Jing, Dongquan; Liu, Yiming; Da, Huijuan; Birnbaumer, Lutz; Yang, Yong; Gao, Xinghua; Gao, Zhenhua; Cao, Qiuhua (Frontiers in Pharmacology, 2024)
During the past half-century, although numerous interventions for obesity have arisen, the condition’s prevalence has relentlessly escalated annually. Obesity represents a substantial public health challenge, especially due to its robust correlation with co-morbidities, such as colorectal cancer (CRC), which often thrives in an inflammatory tumor milieu. Of note, individuals with obesity commonly present with calcium and vitamin D insufficiencies. Transient receptor potential canonical (TRPC) channels, a subclass within the broader TRP family, function as critical calcium transporters in calcium-mediated signaling pathways. However, the exact role of TRPC channels in both obesity and CRC pathogenesis remains poorly understood. This study set out to elucidate the part played by TRPC channels in obesity and CRC development using a mouse model lacking all seven TRPC proteins (TRPC HeptaKO mice). Relative to wild-type counterparts, TRPC HeptaKO mice manifested severe obesity, evidenced by significantly heightened body weights, augmented weights of epididymal white adipose tissue (eWAT) and inguinal white adipose tissue (iWAT), increased hepatic lipid deposition, and raised serum levels of total cholesterol (T-CHO) and low-density lipoprotein cholesterol (LDL-C). Moreover, TRPC deficiency was accompanied by an decrease in thermogenic molecules like PGC1-α and UCP1, alongside a upsurge in inflammatory factors within adipose tissue. Mechanistically, it was revealed that pro-inflammatory factors originating from inflammatory macrophages in adipose tissue triggered lipid accumulation and exacerbated obesity-related phenotypes. Intriguingly, considering the well-established connection between obesity and disrupted gut microbiota balance, substantial changes in the gut microbiota composition were detected in TRPC HeptaKO mice, contributing to CRC development. This study provides valuable insights into the role and underlying mechanisms of TRPC deficiency in obesity and its related complication, CRC. Our findings offer a theoretical foundation for the prevention of adverse effects associated with TRPC inhibitors, potentially leading to new therapeutic strategies for obesity and CRC prevention.